Synthesis, fabrication, characterization, properties and thermal degradation kinetics study of low-K poly(ether-imide)s and co-poly(ether-imide)s, and poly(ether-imide)/MMT clay nanocomposites - ROHITKUMAR H VORA (2010)
Ph.D